Differential gene expression in leaves and roots of Hydrangea serrata treated with aluminium chloride - Scholpp, Anna-Catharina; Schilbert, Hanna Marie; Viehöver, Prisca; Weisshaar, Bernd; Beckstette, Michael; Neumann, Judith Martha; Bednarz, Hanna; Niehaus, Karsten (Frontiers in Plant Science, 2024)
A differential gene expression analysis deciphered transcriptional changes occurring in Hydrangea serrata leaves and roots in response to aluminium chloride treatment. Most differentially expressed genes underlying aluminium response were other than those involved in the phenylpropanoid derived phytoalexin biosynthesis. On the other hand, differential changes in terpenoid and monolignol metabolism genes from H. serrata were detected. The H. serrata 3,4-dihydroisocoumarins, hydrangenol and phyllodulcin harbour a variety of biological activities and pharmacological properties. Therefore, a detailed understanding of dihydroisocoumarin biosynthesis in H. serrata is of major interest. Their biosynthesis is assumed to be enhanced by elicitors and mediated by polyketide synthases like in cases of phenylpropanoid derived phytoalexins. A de novo transcriptome assembly of leaves and roots from the aluminium chloride treatment group versus the control group alongside with annotation was generated. It revealed that a terpene synthase and a triterpenoid synthase gene as well as lignin biosynthesis encoding genes were upregulated in roots. Many genes for transporters, glycosyl-and other transferases as well as glycosylases were found to be differentially expressed in both organs. As no differentially expressed polyketide synthase gene homolog was found, the relative leaf and root 3,4-dihydroisocoumarin content was analysed by LC-MS measurement. Although, Hydrangea species are known for their aluminium detoxification using phenylpropanoid derived compounds the levels of 3,4dihydroisocoumarins were not enhanced. In this metabolite analysis an organ specific accumulation profile of hydrangenol, phyllodulcin, hydrangeic acid and their mono-and diglycosides was figured out.